Development of an Improved Method for the Determination of Iodine/β-Cyclodextrin by Means of HPLC-UV: Validation and the Thyroid-Stimulating Activity Revealed by In Vivo Studies - Avez Sharipov; Zufar Boboev; Sunnatullo Fazliev; Shokhid Gulyamov; Akhmatkhodja Yunuskhodjayev; Jamoliddin Razzokov (MDPI AG, 2021)
Iodine, being an intrinsic part of thyroid hormones, is a vital microelement required for normal growth and development, particularly in children. Inadequate daily intake of iodine causes iodine deficiency, which is responsible for several health disorders, such as cretinism and goiters. Therefore, the development of new drugs and/or food supplements for iodine deficiency is crucial. We synthesized an iodine/β-cyclodextrin complex based on a host-guest model, and in this paper, we outline the development of a new quantitative analysis method. We suggest a robust and reliable high-performance liquid chromatography method to determine the total amount of iodine species in the complex. Moreover, we performed validation of our method. The results of validation presented here show the reliability, accuracy and high precision of the method. Furthermore, for the first time, we show results of in vivo studies for the thyroid-stimulating activity of the iodine/β-cyclodextrin complex. Our findings indicate that the thyroid-stimulating activity of iodine/β-cyclodextrin is comparable to that of potassium iodide, which is the main active pharmaceutical substance of conventional drugs for iodine deficiency.